Transcatheter Aortic Valve Implantation Represents an Anti-Inflammatory Therapy Via Reduction of Shear Stress–Induced, Piezo-1–Mediated Monocyte Activation. Issue 11 (15th September 2020) - Baratchi, Sara; Zaldivia, Maria T.K.; Wallert, Maria; Loseff-Silver, Julia; Al-Aryahi, Sefaa; Zamani, Jalal; Thurgood, Peter; Salim, Agus; Htun, Nay M.; Stub, Dion; Vahidi, Parisa; Duffy, Stephen J.; et al.
Abstract : Background: Aortic valve stenosis is an increasingly prevalent degenerative and inflammatory disease. Transcatheter aortic valve implantation (TAVI) has revolutionized its treatment, thereby avoiding its life-threatening/disabling consequences. Whether aortic valve stenosis is accelerated by inflammation and whether it is itself a cause of inflammation are unclear. We hypothesized that the large shear forces exerted on circulating cells, particularly on the largest circulating cells, monocytes, while passing through stenotic aortic valves result in proinflammatory effects that are resolved with TAVI. Methods: TAVI provides a unique opportunity to compare the activation status of monocytes under high shear stress (before TAVI) and under low shear stress (after TAVI). The activation status of monocytes was determined with a single-chain antibody, MAN-1, which is specific for the activated β2 -integrin Mac-1. Monocyte function was further characterized by the adhesion of myocytes to stimulated endothelial cells, phagocytic activity, uptake of oxidized low-density lipoprotein, and cytokine expression. In addition, we designed a microfluidic system to recapitulate the shear rate conditions before and after TAVI. We used this tool in combination with functional assays, Ca 2+ imaging, siRNA gene silencing, and pharmacological agonists and antagonists to identify the key mechanoreceptor mediating the shear stress sensitivity of monocytes. Last, we stained for monocytes in explanted stenotic aortic human valves. Results: The resolution of high shear stress through TAVI reduces Mac-1 activation, cellular adhesion, phagocytosis, oxidized low-density lipoprotein uptake, and expression of inflammatory markers in monocytes and plasma. Using microfluidics and pharmacological and genetic studies, we could recapitulate high shear stress effects on isolated human monocytes under highly controlled conditions, showing that shear stress–dependent calcium influx and monocyte adhesion are mediated by the mechanosensitive ion channel Piezo-1. We also demonstrate that the expression of this receptor is shear stress dependent and downregulated in patients receiving TAVI. Last, we show monocyte accumulation at the aortic side of leaflets of explanted aortic valves. Conclusions: We demonstrate that high shear stress, as present in patients with aortic valve stenosis, activates multiple monocyte functions, and we identify Piezo-1 as the mainly responsible mechanoreceptor, representing a potentially druggable target. We demonstrate an anti-inflammatory effect and therefore a novel therapeutic benefit of TAVI. Abstract : Supplemental Digital Content is available in the text.